PREVALENCE AND RISK FACTORS OF LOW BACK PAIN AMONG NURSES IN SUDAYR REGION - Al Dajah, Salameh; Al Daghdi, Abdalhamed (European Scientific Journal, ESJ, 2013)
Objective: To study the prevalence and risks of work-related low back pain (LBP) among nurses in Suydar region, Riyadh, Saudi Arabia, and its effect on their regular activities. Subjects and Methods: A self-administered questionnaire (Nordic Musculoskeletal Questionnaire) was distributed to 300 nurses at Suydar region. The questionnaire included demographic data, history and characteristics of LBP before and after working as a nurse, the effect of LBP on regular activities and current LBP. A visual analogue pain scale was used to score the intensity of the pain. Results: Two hundred forty eight (82.66%) of the 300 registered nurses completed the questionnaire; mean age and standard deviation of the respondents were 26.9, 8.45 years. The prevalence of work-related LBP was 53.2%. Moderate pain intensity and were 31.8%. There were positive correlation between pain duration and place of work. The average duration of pain was a week or more (45.6%). Limitation of activities of (n=113) 55.1%. Sick leaves (n=135) 53.9%. Visual analogue scale for measuring the intensity of pain was 38.4% (n=96) of nursing staff scored 5 or more on the scale with average 4.16 of total. Conclusion: Work related prevalence rates of LBP among nurses at Suydar regions is high and affect their daily activities, necessitating changes in work settings and observing there body ergometer with recommendation of back school education.